The effectiveness of the promotional tools done by Aman Palestin Berhad / Nurul Izati Md Jalil and Siti Nur Hidayah Mohd Ali - Md Jalil, Nurul Izati; Mohd Ali, Siti Nur Hidayah (2014)
The purpose of this study was to investigate the relationship of the selected independent variables; advertising, direct marketing, and public relation with dependent variable which is the effectiveness of promotional tools. In order to provide a guide in the study, three hypotheses were formulated. Data were collected from 100 respondents using the questionnaire. This study was conducted at Aman Palestin Berhad. Then the results were analyses by using SPSS to find the significant relationship with the dependent variables. Through this study, it will help Aman Palestin Berhad to identify the new strategy that can be used to increase their promotions strategy.